Transient Analysis of Electromagnetic Wave Interactions on Ferrite Structures using Landau-Lifshitz-Gilbert and Volume Integral Equations - Bin Sayed, Sadeed; Ulku, H. Arda; Bagci, Hakan (IEEE, 2015)
[No abstract available]
USNC-URSI Radio Science Meeting (Joint with AP-S Symposium) Proceedings -- JUL 19-19, 2015 -- Vancouver, CANADA